Living in Refuge: Ritualization and Religiosity in a Christian and a Muslim Palestinian Refugee Camp in Lebanon - Schiocchet, Leonardo (2022)
Living in Refuge is a unique dense socio-historical portrait of two Palestinian refugee camps in Lebanon for which there is almost no recorded literature and that have changed greatly, especially after 2011 and the influx of Syrian refugees. The book compares two contrasting patterns of social belonging in one Muslim Palestinian camp, Al-Jalil, and what, before 2011, was the last Christian Palestinian refugee camp in the world, Dbayeh. Through its unique approach to social belonging processes based on the ritualized rhythm of daily life, it presents and analyses complex discourses, practices, experiences and emotions of life in exile, avoiding simplistic explanations solely based on dogmatic understandings of religion and nationhood. This study shows how moral self-cultivation, piety and religiosity, nationhood, refugeeness and politics are all embedded in each other and frame much of the camps' daily life.